The effect of metergoline on endocrine responses to L-tryptophan. - McCance, S; Cowen, P; Waller, H; Grahame-Smith, D (1987)
The effects of the 5-HT receptor antagonist, metergoline, on the prolactin and growth hormone responses to intravenous L-tryptophan were assessed in seven normal subjects. Pretreatment with metergoline lowered baseline prolactin concentration and abol ished the increase in prolactin following L-tryptophan. In contrast, neither baseline nor the response to L-tryptophan was altered by metergoline. These results are consistent with the proposal that the prolactin response to L-tryptophan is mediated by 5-HT(1) receptors; however, metergoline might also reduce prolactin responses by a dopaminergic action. The nature of the 5-HT receptor involved in the growth hormone response to L-tryptophan remains to be identified.